고전교육의 교육적 성과 분석 연구－역량, 효능감, 흥미 변화를 중심으로 - 권순구; 윤승준 (교양교육연구, 14(5), 2020)
이 연구는 교양교육의 핵심적 주제 가운데 하나인 고전교육에 대한 교육적 성과 확인을 주된 목적으로수행하였다. 이를 위해 A 대학 자유교양대학에서 운영하고 있는 ‘명저읽기’ 강좌를 수강하는 학생을대상으로 고전교육의 성과와 학업적 흥미에 대해 설문조사를 실시하였다. 연구목적을 고려하여 설문조사는 학기 초와 말에 각각 1회씩 실시하였으며, 모든 설문에 성실하게 참여한 학생의 응답(N=600)을최종 분석에 사용하였다. 연구결과, ‘명저읽기’는 고전교육성과 측정도구에서 다루고 있는 모든 역량(독해역량, 의사소통역량, 창의역량)을 향상시키는 데 도움이 되는 것으로 나타났다. 또한, 이 강좌는학생들의 문제해결 효능감을 향상시키는 데에도 도움이 되는 것으로 나타났다. 뿐만 아니라 ‘명저읽기’ 는 학생들의 상황적 흥미와 개인적 흥미를 증진시키는 데 유의미한 효과가 있는 것을 확인할 수 있었다. 이러한 결과는 A 대학 자유교양대학에서 운영하고 있는 ‘명저읽기’ 강좌가 학생들의 관련 역량과효능감, 학업적 흥미를 증진시키는 데 도움이 되도록 효과적으로 운영되고 있다는 것을 시사해준다. 본 연구는 객관적 척도를 활용하여 고전교육의 교육적 성과를 제시한 최초의 연구라는 점에서 의의가있다고 할 수 있다. The main purpose of this study was to confirm the educational performance of classical education as one of the major Liberal Arts courses. To this end, surveys were conducted regarding the achievements of classical education and academic interests for students taking the “Reading Famous Writings” course established at the Liberal Arts College of A university. A survey was conducted once at the beginning, and then at the end, of the semester and responses of students who faithfully participated in all of the surveys were used for the final analysis. As a result of the study, we found that the course helped the students to improve in all areas of competency (reading comprehension, communication competence, and creative competence). In addition, we found the course to be helpful in improving the students’ problem-solving efficacy. Furthermore, we confirmed that this course has a significant effect on enhancing the students’ situational interest and personal interest. These results suggest that the “Reading Famous Books” course is being operated effectively to help increase the students’ related competencies, efficacy, and academic interests. Finally, these findings can be said to be significant in that they are the first studies to present educational outcomes of classical education using an objective scale. Limitations of this study, along with required follow-up studies, were also discussed. KCI Citation Count: 0